UTILIZING MARINE TRAFFIC APPLICATIONS FOR ELECTRONIC NAVIGATION SYSTEMS AND MONITORING COURSES ON CADET REPORTING WHEN IMPLEMENTING MARINE PRACTICE AT MALAHAYATI MERCHANT MARINE POLYTECHNIC - Bayu Yudho Baskoro; Rispa Saeful Mutamar; Syamsul Arifin; Mhd. Hennaufal (Lafadz Jaya Publisher, 2023)
It is undeniable that one of the main causes of the globalization era, which is coming faster than all parties expected, is the rapid development of information technology. The implementation of the internet, electronic commerce, electronic data interchange, virtual office, telemedicine, intranet, and so on has broken through the physical boundaries between countries. The combination of computer technology with telecommunications has produced a revolution in the field of information systems. Data or information that in ancient times had to take days to be processed before being sent to the other side of the world, can now be done in seconds. It is no exaggeration if an IBM expert draws an analogy with automotive developments as follows: